"THE FUTURE OF ARTIFICIAL INTELLIGENCE: OPPORTUNITIES AND CHALLENGES" - Ruzmetova Diana Komilovna; Mamaraimova Durdona Abdusamad qizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation: The future of Artificial Intelligence (AI) presents a complex and evolving landscape, filled with both remarkable opportunities and significant challenges. On the one hand, AI promises to revolutionize industries such as healthcare, finance, education, and transportation by improving efficiency, enabling personalized services, and driving innovation. Advances in machine learning, natural language processing, and robotics are expected to enhance automation, leading to smarter systems and more effective problem-solving capabilities. However, the rapid growth of AI also raises critical concerns, including ethical dilemmas, job displacement due to automation, and privacy issues related to data security. Furthermore, there is the potential for AI to be used maliciously, posing risks in areas such as cybersecurity, warfare, and misinformation.